PENGUJIAN GESER LIMESTONE UNTUK MENGHITUNG ANGKA KEAMANAN TERHADAP KELONGSORAN DI UTAMA MANDALA PURA ULUWATU - Ramia, I Nyoman; Arya, I Wayan; Wiraga, I Wayan; I G A G Suryanegara, I G A G (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2019)
The shear strength value is one of the important points in calculation of slope stability. One way to obtain the shear strength value is to do a direct shear test in laboratory. Like the cliff reinforcement study at Utama Mandala Uluwatu temple which is currently experiencing crack, it is necessary to test the shear strength of the limestone material at the cliff of the temple . There is no limestone testing equipment in the laboratory of the Civil Engineering Department, so that innovation is needed on the existing sliding test equipment. In this study innovation was carried out on how to test the soil shear strength so that it could be used to test the limestone shear strength. The test is done by moving two limestone surface that have been formed based on the mold tool which shape is circle. The shear strength slope at Uluwatu temple, which is currently experiencing crack in dry condition is . The shear strength value is used for calculating slope stability at Uluwatu Temple which is currently experiencing crack wich . The calculation used is curved slope stability by only calculate the life load and dead load. From the calculation of the stability of the slope, the safety factor is 1.15.